Effects of Italian ryegrass silage supplementation on feed intake and behavior of pregnant sows - Makalani, Andrew L.; Kawashima, Tomoyuki; Ishii, Yasuyuki; Takahashi, Toshihiro (Animal Science Journal, 2023)
This study aimed to assess the behavior and stress status of pregnant sows following supplementation with Italian ryegrass silage (IRS) and the impact of feeding the IRS on feeding costs. Six sows with an initial body weight (BW) of 238.6 ± 5.9 kg were allotted to a 6 × 3 Latin square design with a 5‐day acclimatization period followed by a 5‐day data collection period. A commercial diet was replaced by IRS on a dry matter (DM) basis up to 0%, 9%, and 13% in the control treatment and the two test treatments, respectively. Apart from collecting data on daily feed intake and BW, urine was collected, and video footage was recorded for the last day of each treatment for analysis of urinary cortisol and behavior. There were no leftovers with all diets and nutrient uptake was unaffected (p > 0.05), while BW gain decreased (p < 0.05) to be a limited range from 1% to 3%, with increased inclusion of IRS. Both the behavior of sows and cortisol concentration were unaffected (p > 0.05). Furthermore, it was estimated that feeding 13% DM of IRS would reduce feed costs by 17%. IRS would be acceptable in replacing up to 13% of the commercial diet and cutting feeding costs.